Clinical course of tricuspid regurgitation in repaired tetralogy of Fallot. (15th September 2017) - Woudstra, O.I.; Bokma, J.P.; Winter, M.M.; Kiès, P.; Jongbloed, M.R.M.; Vliegen, H.W.; Groenink, M.; Meijboom, F.J.; Mulder, B.J.M.; Bouma, B.J.
Abstract: Background: Little is known on the clinical course of tricuspid regurgitation (TR) in patients with repaired tetralogy of Fallot (rTOF) and which patients are at particular risk. This study aims to determine TR course, characteristics associated with TR progression, and the prognostic relevance of TR in rTOF patients. Methods: In this dualcenter cohort study, rTOF patients from a prospective national registry with ≥ 1 cardiac magnetic resonance imaging study and ≥ 2 echocardiograms available were included. Clinical and imaging data were collected. Cox hazards regression analysis was used to assess patient characteristics associated with progression to severe TR and whether severe TR was associated with the combined clinical endpoint of tachyarrhythmia, heart failure, and death, as time-dependent factor. Results: A total of 216 patients were included (57% men, age 34 ± 12 years); 11 patients (5%) had severe TR at baseline. During 7.6 ± 3.5 years of follow-up, progression to severe TR occurred in 15 patients (7%). NYHA class ≥ 2 (HR 5.38, 95%-C.I. 1.91–15.16, p = 0.001) and moderate baseline TR (HR 13.10, 95%-C.I. 2.95–58.21, p = 0.001) were independently associated with progression to severe TR. Adverse events occurred in 47 patients (22%). The occurrence of severe TR was independently associated with adverse events (HR 3.48, 95%-C.I. 1.68–7.21, p = 0.001). Conclusions: In this study, severe TR was present in 12% of adult rTOF patients during 7.6 years, and progression to severe TR was most likely in symptomatic patients with moderate baseline TR. In these patients, close surveillance is warranted, because the occurrence of severe TR was associated with worse prognosis. Highlights: Severe tricuspid regurgitation occurs in a minority of adult rTOF patients. Symptomatic patients with moderate tricuspid regurgitation are at highest risk. Severe tricuspid regurgitation is associated with worse prognosis. Strategies preventing severe tricuspid regurgitation in rTOF should be considered.